Dharma and Stress: Applied Buddhism for Thai Society in Transition - Fakwang, Phrakhrusangkharak Nuttawut Ciṇṇadhammo (Journal of Dhamma for Life, 2026)
This article aims to study Dhamma and Stress: Applied Buddhism for Thai Society in a Transition Era. In a transitional era of Thai society, which is full of pressures from the economy, technology, and cultural changes, stress has become a common problem that affects people’s quality of life. This research or article aims to study the role of Buddhist principles in relieving stress and to propose guidelines for applying Buddhism to develop mental health at the individual and social levels by using important principles such as the Four Noble Truths, the Four Foundations of Mindfulness, and the Eightfold Path to analyze together with modern psychological concepts. It was found that Dhamma is not only a religious concept, but can also be used as a tool to cope with problems, manage emotions, and develop self-awareness effectively. It was also found that the application of Dhamma in applied Buddhist studies can create a balance between external changes and internal mental states, which is very important for living mindfully in a rapidly changing society. The article suggests that disseminating applied Buddhism in an easily accessible format that is consistent with contemporary life is one approach that can effectively reduce stress at the individual and social levels. Promoting Dhamma learning in an easy-to-understand format that is consistent with contemporary life is a possible approach to reduce stress in Thai society. and is a strong foundation for sustainable development at the mental and social levels.